Synthetic cannabinoids awareness among patients with opioid use disorder in Serbia – A survey based cross-sectional pilot study - Mijatović Jovin, Vesna; Dickov, Isidora; Ratković, Dragana; Dickov, Aleksandra; Tomas, Ana (Frontiers in Psychiatry, 2023)
Introduction There is limited data on the awareness and use of synthetic cannabinoids (SCs) in high-risk population in Serbia, despite SCs becoming more and more common at illicit drug market. Aim This pilot study aimed to examine the awareness and prevalence of use of SCs in patients with an opioid-use disorder and to identify patient characteristics and other factors associated with SCs use. Patients and methods This cross-sectional study was conducted at the Clinic for Psychiatry, Clinical Center Vojvodina, Serbia, the largest tertiary health care institution in this region of the country. All patients hospitalized due to the treatment of opioid dependence during November and December 2017 were included (response rate 100%), and filled-out an anonymous questionnaire specifically developed for the purpose of this study. Differences between patients reporting SCs use and those who did not were compared using chi-square test with values of p < 0.05 were considered significant. Results Out of 64 patients (median age 36.37 years), one third (32.81%) reported using SCs. Socio-demographic characteristics of the subjects were not associated with SCs use. There were differences in the most common sources of information reported between the SCs users and non-users. Majority of SCs users (76.0%) were informed about SCs through friends, compared with just 26.0% of non-users (<0.001). Nearly all study participants (93.8%) were daily tobacco users. The share of respondents reporting alcohol and marihuana use was significantly higher among the SCs users (52.0% vs. 20.9%, p = 0.011 and 15.6% vs. 12.5%, p = 0.015), respectively. Higher share of SCs users used multiple psychoactive substances (38.1% vs. 16.3%), and this difference was statistically significant (p = 0.047). The most commonly reported adverse effect of SCs among users included dry mouth (81.0%), trouble thinking clearly (52.4%) and panic attacks (52.4%). Conclusion Understanding the awareness and use of SCs among high-risk drug users, as well as associated factors can help improve substance-use disorder treatment in our setting. Educational activities targeting public are urgently needed to raise awareness on SCs, considering that social contacts are the main sources of information on SC for this vulnerable population. Users of SCs have also reported using other psychoactive substances more often, and this calls for a holistic approach addressing multiple factors to improve substance-use treatment in our setting.